2018
DOI: 10.28991/cej-03091132
|View full text |Cite
|
Sign up to set email alerts
|

Numerical and Experimental Research on Convergence Angle of Wet Sprayer Nozzle

Abstract: Shotcrete is a popular support method in construction of both ground projects and underground projects, such as tunnels, subways, slopes and roadway, etc. However, at present researches on the influence of nozzle structure parameters on the performance of concrete injection are insufficient. This research focuses on the influence of various parameters of nozzle structure on the evenness and dust generating, and conducts a systematic study on the flow characteristics of the concrete in the nozzle of wet sprayin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 11 publications
(11 reference statements)
0
3
0
Order By: Relevance
“…They concluded that the results predicted by the CFD software generally are consistent with the literature data for different nozzle pressure ratios (NPRs). Su and Cheng [10] conducted numerical and experimental research on the convergence angle of the wet sprayer nozzle. They investigated a convergent nozzle with a cone-half angle between 3° and 7° used in a shotcrete operation for the construction of both ground projects and underground projects, such as tunnels, subways, slopes, roadways, etc.…”
Section: Introductionmentioning
confidence: 99%
“…They concluded that the results predicted by the CFD software generally are consistent with the literature data for different nozzle pressure ratios (NPRs). Su and Cheng [10] conducted numerical and experimental research on the convergence angle of the wet sprayer nozzle. They investigated a convergent nozzle with a cone-half angle between 3° and 7° used in a shotcrete operation for the construction of both ground projects and underground projects, such as tunnels, subways, slopes, roadways, etc.…”
Section: Introductionmentioning
confidence: 99%
“…Jalali et al [14] observed that higher heat transfer coefficient was achieved by using 2.5 wt % Al2O3 nano-fluids compared to 1.0 wt % Al2O3 nanofluids. There is also research on the production of hybrid nanoparticles and its effect on increasing heat transfer [15][16][17][18]. Shokouhmand et al [19] investigated convective heat transfer and laminar flow by using lattice boltzmann method (LBM) in two channel configurations in a canal full of an inserting porous.…”
Section: Introductionmentioning
confidence: 99%
“…The study of non-Newtonian fluid flow has been appealing many interests, due to its numerous industrial and engineering applications including polymer technology, condensed matter physics, astrophysics, geophysics, environmental, biophysics and molten plastics, etc. Furthermore, according to literature, the subject of the MHD fluid flows have been considered in many research works using different methods [1][2][3][4][5], and fluid flow in the nozzle has been investigated with different methods as well [6,7]. Makinde [8] investigated the effect of arbitrary magnetic Reynolds number on a steady flow of an incompressible conducting viscous liquid in divergent channels under the influence of an externally applied homogeneous magnetic field.…”
Section: Introductionmentioning
confidence: 99%